PERMAINAN ULAR TANGGA DALAM KARYA GRAFIS - Eliya Pebriyeni, S.Pd., M.Sn., FADLAN FAHROZI, Ir. Drs. Heldi, M.Si., (Serupa The Journal of Art Education, 2016)
Human beings have an unlimited power of imagination. The human being tried to make them into reality and make people complacent in the fantasy life. When a person feels that is not as wish as they hope, he can express it in the body language, facial expressions and behavior. A person could be not himself and was stuck in fantasy that’s created. On the way to reach the goal, that is not only sweet and happy perceived. Sometimes sadness, disappointment, hurt, and bored become the colorful in the process of achieving a sense.This art work aims to reveal the expression and psychological feelings of snakes and ladders game players with all sorts of issues and problems perceived. Methods and steps in the process of cultivating this art work begins with the preparation, elaboration, synthesis, until the realization of the concept that is presented to the public with exhibits.The author visualizes the self-expression in a game of snakes and ladders with the technique of serigraphy to provide information to the audience of graphic art about feeling that is contained on this game via the ten works with the title: mengawali langkah, di tinggal lawan, meninggalkan lawan, kompetisi, di tinggal rombongan, histeris, dihantui, ketakutan, bingung, mendekati kemenangan, menang.Key word: Expression, A Game of Snakes and Ladders, Graphic Art, Serigraphy